A Pilot Study on the Effects of Mindfulness-Based Journaling on the Psychological Well-Being of Preschoolers' Parents - Hita Lafia Sarasvati; Ribut Purwaningrum; Naharus Surur; Suwarjo (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Preschoolers' parents often face psychological challenges that can affect their well-being and caregiving. Mindfulness-based journaling may offer a practical and accessible strategy to support psychological well-being. This pilot study used a mixed-methods design to evaluate the feasibility and preliminary effectiveness of a mindfulness-based journaling program for prechoolers’ parents in Indonesia. Twenty participants completed six days of guided journaling based on Ryff’s six dimensions of psychological well-being. Quantitative data were collected using the Indonesian-adapted version of the Ryff Psychological Well-Being Scale (RPWBS) and analyzed using the Wilcoxon signed-rank test and normalized gain scores. Results showed statistically significant improvements across all dimensions, though normalized gain indicated low practical effectiveness A thematic analysis of participants’ journal entries was conducted using deductive and inductive approaches. Participants generally found the intervention helpful, with several expressing a willingness to continue journaling independently. While the short duration and reliance on self-report limit generalizability, this study provides initial support for mindfulness-based journaling as a feasible, low-intensity approach to promoting parental well-being. Future research should explore longer interventions with diverse samples and include follow-up assessments to evaluate sustained effects.